Child protection procedures in emergency departments. Issue 12 (20th November 2007) - Sidebotham, P; Biu, T; Goldsworthy, L
Abstract : Background: Emergency departments (EDs) may be the first point at which children who have been subject to abuse or neglect come into contact with professionals who are able to act for their protection. In order to ascertain current procedures for identifying and managing child abuse, we conducted a survey of EDs in England and Northern Ireland. Methods: Questionnaires were sent to the lead professionals in a random sample of 81 EDs in England and 20 in Northern Ireland. Departments were asked to provide copies of their procedures for child protection. These were analysed qualitatively using a structured template. Results: A total of 74 questionnaires were returned. 91.3% of departments had written protocols for child protection. Of these, 27 provided copies of their protocols for analysis. Factors judged to improve the practical usefulness of protocols included: those that were brief; were specific to the department; incorporated both medical and nursing management; included relevant contact details; included a single page flow chart which could be accessed separately. 25/71 (35.2%) departments reported that they used a checklist to highlight concerns. The most common factors on the checklists included an inconsistent history or one which did not match the examination; frequent attendances; delay in presentation; or concerns about the child's appearance or behaviour, or the parent–child interaction. Conclusions: There is a lack of consistency in the approach to identifying and responding to child abuse in EDs. Drawing on the results of this survey, we are able to suggest good practice guidelines for the management of suspected child abuse in EDs. Minimum standards could improve management and facilitate clinical audit and relevant training.